Functional and Structural Features of Organizing the "Sense of Rightness" within the Structure of Personality - Bogachenko, Yuliia (Psychological Counseling and Psychotherapy, 2024)
The article investigates the problem of organizing the "sense of rightness" in the structure of personality in the context of modern challenges, particularly the war in Ukraine, which has led to deteriorating psychological health, increased stress levels, and the emergence of various psychological symptoms. The authors emphasize the importance of internal harmony and authenticity of personality in the conditions of an increasing pace of life and informational influence. The concept of Carl Rogers' "organismic tendency," which focuses on the internal sense of rightness supported by a therapeutic environment, is examined. Approaches of other theorists, such as Leslie Greenberg, Robert Elliott, Erik Erikson, Lawrence Kohlberg, and Viktor Frankl, regarding the formation and maintenance of the "sense of rightness" are also analyzed. The study highlights the necessity of new therapeutic methods to support psychological resilience and personality development under modern stress factors, particularly through emphasizing the integration of emotions, self-awareness, and the search for deep meaning in life and the sense of rightness.